ROLE OF SOCIAL STUDIES INSTRUCTIONS IN CURBING TRUANCY AMONG UPPER BASIC STUDENTS IN KWARA STATE, NIGERIA - Olokooba Issa Nasiru; Balogun Idayat Nike; Adegboye Surajudeen Olayiwola (Sanata Dharma University Yogyakarta, 2025)
Truancy is an anti-social behaviour and its prevalence in upper basic schools in Nigeria is alarming. Social Studies as a problem-solving discipline is one of the best ways of curbing truancy. The study therefore assessed role of Social Studies instructions for curbing truancy among upper basic students in Kwara State in Nigeria. The specific objectives were to investigate the forms, causes, consequences and ways of curbing truancy. A descriptive survey research design was employed. A self-structured questionnaire entitled “Assessment of Social Studies Instructions for Curbing Truancy” with 0.73 reliability index obtained through test-retest method was employed. Four research questions were raised and answered using mean ranking. The findings of the study revealed that the forms of truancy among upper basic students included truant behaviour resulting from dislike of subject teacher and repeated absence from school for a complete term among others. The causes of truancy were peer pressure and overpopulation among others. Consequences of truancy were found to include poor academic performance, student drop out and cultism among others. The discipline inculcated in students’ obedience to rules of school, attendance, punctuality and participation in school activities. It was recommended that parents should collaborate with schools on truancy prevention and intervention programs as it is clear that home factors contribute significantly to truant behavior exhibited by students.